Rare case of multisystemic Klebsiella pneumoniae infection in a diabetic patient: a case report - Bin, Xiaochang; Tang, Fen; Zou, Li; Lv, Jian; Luo, Yanjie; Tang, Zhenqiang (Frontiers in Endocrinology, 2026)
BackgroundMultisystemic infections caused by Klebsiella pneumoniae (Kp) are rare but can be life-threatening, particularly in patients with diabetes mellitus (DM). We report a case of a 65-year-old diabetic female patient who developed concurrent ocular, intracranial, hepatic, and pulmonary abscesses caused by K. pneumoniae.Case presentationThe patient presented with a subacute onset of cough, fever, and ocular symptoms. The diagnosis was confirmed through integrated clinical assessment, laboratory analysis, and multimodal imaging. The patient’s condition was momentarily improved following enucleation of the infected eye and initial empirical therapy with meropenem and vancomycin, followed by targeted antimicrobial treatment based on the microbiological results. Regular follow-up with serial cranial magnetic resonance imaging (MRI) scans was performed to monitor disease progression and response to treatment.ConclusionThis case highlights the critical necessity for early diagnosis, aggressive surgical intervention, and prolonged antimicrobial therapy in diabetic patients with severe Kp dissemination. Comprehensive clinical and radiological follow-up is paramount to ensure therapeutic efficacy and recovery.